Rancang Bangun Sistem E-Voting Berbasis Web Untuk Pemilihan Ketua RW Pada Kelurahan dengan Metode RAD - Anwar Tonggo Sitorus (Journal of Informatics Management and Information Technology, 2025)
This study aims to determine the simultaneous RW chairman election system in Pekayon Jaya Village, South Bekasi Subdistrict, Bekasi City. And to find out the obstacles faced in the process of simultaneous RW chairman election in Pekayon Jaya, South Bekasi Subdistrict, Bekasi City. The election process so far still uses conventional voting, namely by using paper media for the election process and manually calculating the election results, so that the calculation of election results is relatively long and calculations sometimes still occur errors. Advances in information technology today have brought considerable changes to humans, including the way to carry out voting. The use of computer technology in voting is known as electronic voting or e-voting, so that the election process becomes faster and more efficient. This system is designed using the research and development method used in this research is Rapid Application Development (RAD) with the PHP programming language, Sublime Text 3, and the database files are designed using MySQL Xampp. The design of this information system is made to help, simplify, and anticipate errors that occur in the selection of RW Chairmen. Blackbox testing results show that the functions in the software can run properly and no errors are found. Feasibility testing includes system quality, information quality, service quality, intensity of use, user satisfaction, and benefits obtained. The test results of this e-voting system in the user test included a very good category. Therefore, the e-voting system is feasible to use, with future improvements.